Combination of high resolution melting (HRM) analysis and SSR molecular markers speeds up plum genotyping: case study genotyping the Greek plum GeneBank collection. Issue 4 (3rd March 2016) - Merkouropoulos, Georgios; Ganopoulos, Ioannis; Tsaftaris, Athanasios; Papadopoulos, Ioannis; Drogoudi, Pavlina
Abstract: In a germplasm bank collection the conservation and characterization of genetic resources is a prerequisite in order to use the material in breeding projects aiming the creation of new cultivars. In the present study, 54 Prunus salicina domestica and Prunus domestica genotypes (including seven Greek cultivars), maintained in the ex situ National Genebank Collection of Greece, were classified using microsatellite (simple sequence repeat, SSR) markers on high resolution melting (HRM) analysis. The SSR primer pairs were chosen from the published literature as originally designed on Prunus species. This combined approach was used to genotype all plum accessions of the collection highlighting the benefits of either method (HRM and SSRs) for cultivar identification. Dendrograms for P. domestica and P. salicina and a combined one with all the genotypes assayed were produced. A total of 15 from the 19 P. domestica accessions analysed, including all the Greek accessions but 'Avgati Skopelou', were grouped into the same clade in the combined dendrogram, whereas the remaining four were dispersed into the P. salinica clades. Bayesian structure analysis confirmed that 'Avgati Skopelou' differs from the rest of the Greek plum cultivars since it was not grouped into the same cluster. The combination of HRM and SSRs, provided a considerably faster, cost-effective, closed-tube microsatellite genotyping method for molecular characterization of plum cultivars.